Variation in cellular EGF receptor mRNA expression demonstrated by in situ reverse transcriptase polymerase chain reaction. - Heniford, B W (1993)
Cell to cell variation of epidermal growth factor (EGF) receptor mRNA levels in heterogeneous tissues has been demonstrated with an in situ assay that couples reverse transcriptase with the polymerase chain reaction (in situ RT-PCR). EGF receptor mRNA is consistently more highly expressed in regions where cell division occurs; EGF receptor mRNA is markedly reduced if not absent in areas of squamous cell differentiation. Both human and mouse tumors overexpress EGF receptor mRNA when compared to normal tissue. In situ RT-PCR performed on thin sections obtained from cell pellets of cultured cells with known levels of EGF receptor mRNA expression demonstrated that the mRNA detected is consistent with that observed by Northern analysis and quantitative PCR on isolated RNA and by protein levels detected by antibody binding assays. In situ RT-PCR is significantly more sensitive than in situ hybridization (ISH). The method avoids background associated with hybridization reactions as in ISH or ISH following in situ PCR. In situ RT-PCR appears to be applicable to any gene as long as the oligonucleotide primers used have been proven to be specific and effective in a standard RT-PCR assay.